2018
DOI: 10.21315/tlsr2018.29.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Incorporation of Jackfruit Rind Powder on Chemical and Functional Properties of Bread

Abstract: Nowadays, there is a rising interest towards consuming health beneficial food products. Bread–as one of the most popular food products–could be improved to ‘healthy bread’ by addition of ingredients high in protein, dietary fiber and low in calorie. Incorporating Jackfruit rind powder (JRP) as a by-product rich in dietary fiber in bread, could not only provide health beneficial bread products, but also lead to develop an environmental friendly technology by solving the problem of waste disposal of residues. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
6
1
1
Order By: Relevance
“…[13,17] Some studies found that hardness had a significant correlation with cohesiveness and springiness. [33] However, our results revealed that these parameters had no significant relationship, which could be hypothesized because of the different materials.…”
Section: Correlation Between Thermal Freezable Water Content Rheological and Technological Propertiescontrasting
confidence: 56%
See 1 more Smart Citation
“…[13,17] Some studies found that hardness had a significant correlation with cohesiveness and springiness. [33] However, our results revealed that these parameters had no significant relationship, which could be hypothesized because of the different materials.…”
Section: Correlation Between Thermal Freezable Water Content Rheological and Technological Propertiescontrasting
confidence: 56%
“…[9] However, few researchers reported that extruded wheat bran and jackfruit rind flour decreased the springiness or cohesiveness of bread due to the inclusion of non-gluten flour. [32,33] Total polyphenol content and antioxidant activity properties of steamed bread There was a significant difference in the total polyphenol content (TPC) and antioxidant activity of composite steamed breads, the TPC value in decreasing order was Control<UP<EP at the same level (Figure 2). The amount of TPC and antioxidant activity improved with substitution levels increasing.…”
Section: Specific Volume Of Steamed Breadmentioning
confidence: 98%
“…For example, some by-products have been used as antibrowning additives due to their high content of organic acids (ascorbic, malic, and phosphoric acid) and phenolic compounds; as antimicrobial mainly due to their essential oils and phenolic compounds, or as a source of specific BCs such as DF, PCs or specific minerals (Ayala-Zavala et al, 2011; Olivas-Aguirre et al, 2017). Some bakery products have been enriched with by-products, such as is the case of cakes enriched with DF and protein content using potato peel powder (Ben Jeddou et al, 2017) and apple pomace (Sudha et al, 2007); dough biscuits with DF enriched with PCs and carotenoids using mango peel powder (Ajila et al, 2008); gluten-free cookies with DF using plantain peel flour (García-Solís et al, 2018); cookies and bread with DF using unripe mango fruit (Vergara-Valencia et al, 2007); bread with DF using jack fruit rind powder (Felli et al, 2018); and bread, muffins and brownies with DF and enriched with PCs using wine grape pomace (Walker et al, 2014) among others ( Table 1).…”
Section: Use Of Agro-industrial By-products In Bakery Productsmentioning
confidence: 99%
“…Es considerada como la fruta más grande del mundo ya que llega a pesar hasta 50 kg, por lo cual su consumo y procesamiento producen importantes cantidades de cáscaras y semillas. En particular, las semillas de jaca poseen siete veces más FD que la harina de trigo [26]. Ramya y col. [27] desarrollaron galletas sustituyendo parcialmente harina de trigo (5, 10 y 15%) con harina de semilla de jaca (HSJ).…”
Section: Camú-camúunclassified